2010
DOI: 10.1038/sj.bjc.6605973
|View full text |Cite
|
Sign up to set email alerts
|

Improving the accuracy of pre-operative survival prediction in renal cell carcinoma with C-reactive protein

Abstract: Background:Validated objective biomarkers are needed for patients with renal cell carcinoma (RCC) to guide patient management and define high-risk populations for follow-up or for therapeutic purposes.Methods:Patients undergoing nephrectomy for RCC (n=286 all stages, 84% with conventional clear cell type) were included with a median duration follow-up of 5 years. The prognostic significance of pre-operative haematological and biochemical variables, including C-reactive protein (CRP) values were examined and wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
45
2
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(49 citation statements)
references
References 30 publications
1
45
2
1
Order By: Relevance
“…Other prognostic factors, such as the preoperative thrombocyte count, were demonstrated in a study of non-metastatic RCC [28] . It is also noteworthy that although a large amount of studies found that CRP [29][30][31][32][33][34][35] is an important predictive factor for survival in patients with RCC, a study from Bedke et al [36] concluded that inflammatory prognostic markers such as preoperative CRP do not improve predictive accuracy in a heterogeneous clear cell renal cell carcinoma study group. However, in our mRCC/ CN study group, preoperative CRP was indeed able to improve the overall accuracy of the established MSKCC scoring system indicating the importance of this inflammatory marker, particularly in metastasized RCC patients.…”
Section: Discussionmentioning
confidence: 99%
“…Other prognostic factors, such as the preoperative thrombocyte count, were demonstrated in a study of non-metastatic RCC [28] . It is also noteworthy that although a large amount of studies found that CRP [29][30][31][32][33][34][35] is an important predictive factor for survival in patients with RCC, a study from Bedke et al [36] concluded that inflammatory prognostic markers such as preoperative CRP do not improve predictive accuracy in a heterogeneous clear cell renal cell carcinoma study group. However, in our mRCC/ CN study group, preoperative CRP was indeed able to improve the overall accuracy of the established MSKCC scoring system indicating the importance of this inflammatory marker, particularly in metastasized RCC patients.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous serum inflammation markers, such as CRP [6][7][8][9][10], have proven to be good prognostic indicators in patients with a variety of malignancies, but they require separate laboratory testing. The easily calculated NLR, on the other hand, has shown utility as an alternative marker of systemic inflammation in critically ill patients [19], malignancies [20], and chronic medical conditions such as end-stage renal disease and diabetes [21][22][23].…”
Section: Discussionmentioning
confidence: 99%
“…There is now an ample body of literature on the association between chronic inflammation and cancer [1][2][3][4], with an estimated 15% of malignancies worldwide being reported as having an infectious association or etiology [5]. C-reactive protein (CRP), a serum marker for systemic inflammation, has shown good prognostication in patients with renal cell carcinoma (RCC) [6][7][8][9][10] and similar findings when combined with serum albumin levels in the modified Glasgow Prognostic Score [3]. However, CRP requires additional serum testing and hence is not readily available for all patients.…”
Section: Introductionmentioning
confidence: 99%
“…2 Renal cell carcinoma (RCC) accounts for approximately 85% of all renal malignancies. 3 Over three quarters of patients will have localised disease at time of diagnosis 4,5 and may be candidates for nephrectomy with curative intent. Despite resection of localised disease, a significant proportion of patients will subsequently develop metastatic disease.…”
Section: Introductionmentioning
confidence: 99%